2001
DOI: 10.1034/j.1399-0039.2001.580306.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐B*51 allele analysis by the PCR‐SBT method and a strong association of HLA‐B*5101 with Japanese patients with Behçet’s disease

Abstract: Behçet's disease (BD) is known to be associated with human leukocyte antigen (HLA) B51 in many different ethnic groups. An increased incidence of HLA-B51 in the patient group has also been reported in a Japanese population. Recently, the B51 antigen has been identified to comprise 21 alleles, B*5101-B*5121. Further, not only HLA-B*5101 but also HLA-B*5108 were found to be relatively increased in the patient groups among Italian and Saudi Arabian populations. Therefore, we performed HLA-B*51 allele genotyping b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 13 publications
2
40
0
1
Order By: Relevance
“…Mizuki et al suggested that a genetic predisposition to BD appears to play an important role with a strong association with the MICA gene rather than HLA B51 (6), but a recent report has suggested that the real pathogenic gene for BD is the HLA-B gene itself and the HLA-B * 51 allele is the major susceptibility gene responsible for the development of BD (4,13,15,22). Therefore, we cannot be certain whether HLA-B51 itself or a closely linked gene is responsible for the susceptibility to BD.…”
Section: Discussionmentioning
confidence: 99%
“…Mizuki et al suggested that a genetic predisposition to BD appears to play an important role with a strong association with the MICA gene rather than HLA B51 (6), but a recent report has suggested that the real pathogenic gene for BD is the HLA-B gene itself and the HLA-B * 51 allele is the major susceptibility gene responsible for the development of BD (4,13,15,22). Therefore, we cannot be certain whether HLA-B51 itself or a closely linked gene is responsible for the susceptibility to BD.…”
Section: Discussionmentioning
confidence: 99%
“…In many populations, HLA-B5101 has been identified as the major subtype of HLA-B51 (González-Escribano et al, 1998;Mizuki et al, 2001;Paul et al, 2001). HLA-B5101 positivity has been reported to be 62-98% in various populations (Suzuki and Suzuki, 2004).…”
Section: Hla-b51 Subtypes In Behçet's Diseasementioning
confidence: 99%
“…The genotype of HLA-B51 has been analyzed in BD patients in various countries [19][20][21][22][23][24][25]; 21 alleles were identified for HLA-B51 molecules, designated as HLA-B*5101 to B*5121. Studies in ten countries along the Silk Road disclosed that 26%-77% of patients were HLA-B51 positive.…”
Section: Hla-b51mentioning
confidence: 99%